Trained immunity as a novel therapeutic strategy. (August 2018) - Mourits, Vera P; Wijkmans, Jac CHM; Joosten, Leo AB; Netea, Mihai G
Highlights: Trained immunity reprograms innate immune responses in humans. Trained immunity plays a role in the pathophysiology of immune-mediated diseases. Targeting trained immunity is a novel promising therapeutic strategy. Abstract : Recent studies have shown that upon certain vaccinations or infections human innate immune cells can undergo extensive metabolic and epigenetic reprogramming, which results in enhanced immune responses upon heterologous re-infection, a process termed trained immunity . Trained immunity has also been shown to be inappropriately activated in inflammatory diseases. This provides the potential for identifying novel therapeutic targets: potentiation of trained immunity could protect from secondary infections and reverse immunotolerant states, while inhibition of trained immunity might reduce excessive immune activation in chronic inflammatory conditions. By targeting specific mechanisms of trained immunity on either immunologic, metabolic or epigenetic level, novel therapeutic approaches could be developed.